2022
DOI: 10.2147/jir.s379349
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell RNA Sequencing Reveals the Immune Cell Profiling in IMQ Induced Psoriasis-Like Model

Abstract: Purpose Psoriasis is a chronic systemic inflammatory skin disease with a high recurrence rate. The immune response plays an important role in psoriasis. However, the subsets of immune cells involved in inflammation in psoriatic mice have not been fully studied. This study showed the immune environment characteristics of psoriasis in mice. Methods We used single-cell RNA sequencing (10× Genomics) as an unbiased analytical strategy to investigate the heterogeneity of skin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 54 publications
2
4
0
Order By: Relevance
“… 7 Recently, single-cell RNA sequencing revealed that macrophages were the main group of immune cells in IMQ-induced psoriasis mice. 25 Our study also found that the percentage of macrophages in skin lesions was prominently elevated, about 61.29%, which is similar to what was previously reported. The extensive infiltration of macrophages in psoriasis lesions deserves further investigation to elucidate the relationship between macrophage levels and activities and the pathogenesis of psoriasis.…”
Section: Discussionsupporting
confidence: 92%
“… 7 Recently, single-cell RNA sequencing revealed that macrophages were the main group of immune cells in IMQ-induced psoriasis mice. 25 Our study also found that the percentage of macrophages in skin lesions was prominently elevated, about 61.29%, which is similar to what was previously reported. The extensive infiltration of macrophages in psoriasis lesions deserves further investigation to elucidate the relationship between macrophage levels and activities and the pathogenesis of psoriasis.…”
Section: Discussionsupporting
confidence: 92%
“…Across both tSNE and UMAP plots, cell types were more widespread in IMQ samples compared to control samples, revealing the diversity in heterogenous cell identity, which was also indicated by previous research [ 20 ] that used different gene markers for each cell type.…”
Section: Resultssupporting
confidence: 72%
“…Across other studies, many different resolutions were used to identify cell cluster groups, with the most used being a 0.5 resolution [ 20 , 21 ]. However, when implementing a 0.5-resolution tSNE plot with the single-cell RNA sequencing data, too few cell clusters were identified as unique, resulting in the loss of many cell groups.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…As an autoimmune disease, various cells, including KCs, FBs, pDCs, NKT cells, and macrophages, are involved in the entire immune process of psoriasis [ 3 , 4 ]. Jin et al used scRNA-seq to reveal the immune cell spectrum of IMQ-induced mice with psoriasis and observed that the proportions of macrophages, NK/T cells, cDCs and pDCs were increased in IMQ-treated mice compared with WT mice [ 27 ]. In our scRNA-seq analysis, the proportion of KCs and FBs showed the most significant difference, which indicated that KCs and FBs played important roles in the pathogenesis of psoriasis.…”
Section: Discussionmentioning
confidence: 99%